General surgery service with limited feasibility in a rural hospital; Retrospective cohort study - Başak, Fatih (Journal of Surgery and Medicine, 2018)
Aim: Many residents living in rural areas have access to health services more difficult than those living in urban areas. Although 20% of the US population lives in rural areas, only 9% of physicians work in these areas, and in particular general surgeons appear to be inadequate in small rural towns. This study was planned in order to determine the applications made from the general surgery in the district state hospital. Methods: The study was carried out at the Bozkır State Hospital with 25 beds located approximately 150 km away from the center of Konya. In 2009, patient files were reviewed for general surgery polyclinic. Elective and urgent (major and minor) operations were recorded. The results are examined. Results: During the study period, 4312 patients were seen in the outpatient clinic. The total number of working days in 2009 is 224 and the average number of patients per day is 22. During the study period, 35 major operations were performed. Twelve appendectomies, 15 inguinal hernias, six pilonidal sinus, one goiter and one intestinal resection in a case with strangulated inguinal hernia were performed. Conclusion: The experience we have in our hospital may be related to the social structure and needs of our region. A rural surgeon, like third-line hospital services, may need experienced teams and adequate infrastructure to confront patients and meet their needs.